Этика: учебник для филос. фак. вузов / Под общ. ред. А. А. Гусейнова и Е. Л. Дубко - Гусейнов Абдусалам Абдулкеримович (Disciplinae, 1999)
Экземпляры: ЦБ (2001) / Инвентарный номер: 33765 / Цена: 57.00 / Сис.шифр: 87.7я7 / Авт.знак: Э 90 / ГРНТИ: 02.51 / ББК: 87.7я7